Model Pembelajaran Interaktif dalam Meningkatkan Keterampilan Literasi Membaca dan Menulis Siswa di Sekolah Dasar - Tangkudung, Mutmain; Zakarina, Uznul; Gafur, Dea Amanda; Maladja, Elsa Daeng; Akuba, Adelia (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The learning model is a support for the learning process, for this reason, its use is important in the implementation of learning. This study aims to describe the use of interactive learning models in elementary schools in improving students' reading and writing skills. The method used in the study is qualitative descriptive to determine the use of interactive media in learning in elementary schools. The results of the study show that the application of the interactive learning model in schools is carried out quite optimally and has contributed positively to improving students' reading and writing skills. Schools that implement an interactive learning model carry out teacher training, and provide facilities to support the implementation of the program.